Optimalisasi Penjadwalan Proyek Pembangunan Gedung Puskesmas Badas Menggunakan Critical Path Method-Project Evaluation and Review Technique (CPM-PERT) - Dafid Cahya Setiawan; Ahmad Ridwan; Suwarno Suwarno (Faculty of Engineering, Kadiri University, 2021)
Lack of project scheduling planning and ineffective control make the activity of a project less efficient. This will have an impact on the success of the project. This situation will result in delays and a decrease in the quality of work due to time constraints. Scheduling is important for determining the required activities and arranging a sequence and time frame to complete project activities on time. This study aims to optimize the scheduling of a moderate light rehabilitation project in the Badas Community Health Center building, Kediri Regency, where project start-ups are experiencing delays. The method used is Critical Path Method-Project Evaluation and Review Technique (CPM-PERT), which is a method to determine the duration of a project that can be completed and the percentage of its success. The analysis carried out includes calculation the duration desired acceleration and cost slope. Analysis results using CPM-PERT obtained critical path in: preparation activities (A), earthworks (B), structural work (D), 1st floor work (E), 2nd floor work (F), 3rd floor work (G), roof, ceiling and plank work (H), iron work (I), electrical work (L), floor and wall covering work (M) and finishing work (N). The normal duration of project completion is 140 days and costs Rp. 1,818,182,709, whereas with the CPM-PERT method the duration can be accelerated to 128 days (probability 99.99%) and required additional fee 8.1% or worth Rp. 146,719,664. Implementers can use it in optimizing scheduling and financing on the badas public health center building construction project.